2022
DOI: 10.1039/d1ta10559k
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum vapor migration strategy for atom–nanoparticle composite catalysts boosting bifunctional oxygen catalysis and rechargeable Zn–air batteries

Abstract: Reasonable design of bifunctional catalysts for oxygen reduction reactions (ORR) and oxygen evolution reactions (OER) is of great importance for the large-scale deployment of metal-air batteries. Herein, we developed a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…It was reported that the catalytic Co active sites can promote the graphitization of carbon in high temperature pyrolysis. 48–50 Fig. 1f shows the high-resolution TEM image of an embedded Co 3 O 4 nanoparticle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the catalytic Co active sites can promote the graphitization of carbon in high temperature pyrolysis. 48–50 Fig. 1f shows the high-resolution TEM image of an embedded Co 3 O 4 nanoparticle.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the catalytic Co active sites can promote the graphitization of carbon in high temperature pyrolysis. [48][49][50] Fig. 1f 2b, which correspond to the edge, distorted carbon and structure defects (D-band) and the graphitic sp 2 carbon (G-band), respectively.…”
Section: Fabrication and Testing Of Flexible Quasi-solid-state Rzabsmentioning
confidence: 99%
“…As for PtCo/Co–N–C, metallic Co 0 emerges and the ratio of Co–N x decreases apparently, fully proving that the Co–N x bonds are broken, and the Co atoms are segregated into the lattice of Pt after annealing under a H 2 /Ar atmosphere. In addition, PtCo/Co–N–C (780.70 eV) shows a positive shift in the binding energy of Co 2p 3/2 compared to Pt/Co–N–C (780.10 eV), implying that the electronic structure of Co is modulated, which may be induced by the enhanced metal–support interplay between PtCo nanoparticles and Co–N–C carriers . The high-resolution Pt 4f XPS spectra can be split into Pt 4f 7/2 and Pt 4f 5/2 , containing Pt(0) and Pt­(II), in which Pt(0) is considered to be the main active center of the ORR process.…”
Section: Resultsmentioning
confidence: 99%
“…Within this context, it is of practical value to design a highly efficient and durable bi-functional ORR–OER catalyst for ZABs. 9–11…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, it is of practical value to design a highly efficient and durable bi-functional ORR-OER catalyst for ZABs. [9][10][11] Recently, carbon/transition-metal phosphide (TMP) nanohybrids with nanoconnement structures have received extensive and continuous interest because of their unique features of spatial connement and functional integration, thus making them attractive for potential utilization in energy-related electrocatalysis areas. 12,13 Many early studies have demonstrated that constructing these N-doped carbon (NDC) frameworks with conned phosphide-based moieties represents a feasible strategy to ne-tune the electronic interactions between the embedded metal phosphide particles and their adjacent carbon-based substrates, thereby enhancing the intrinsic activities of the catalysts.…”
Section: Introductionmentioning
confidence: 99%